Knowledge, attitudes, and practices regarding drug allergy among healthcare providers in Eastern India - Deependra Kumar Rai; Pramod Kumar Manjhi; Rathis Nair (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Drug allergy (DA) or hypersensitivity is an immunologically mediated reaction producing stereotype symptoms which is challenging for health care providers (HCP). Objective of current study was to assess the knowledge, attitudes and practices of drug allergy among healthcare providers in eastern India. Methods: A 25-item self-administered DA questionnaire was developed and applied in our study. The questionnaire covered 3 domains: knowledge, attitudes, and practice patterns. From July 2020 to September 2020, HCPs participated in the cross-sectional study. Results: A total of 237 HCPs participated in the study, and all questionnaires were analysed. Among the respondents, 226 (95.4%) were nurses, 9 (3.8%) were doctors and 2 (0.8%) were pharmacists. The majority of HCPs agreed that drug-induced immediate allergic reactions were IgE mediated 225 (94.9%), occur within 6 hours of drug administration (89.9%), and epinephrine was the first choice for drug-induced anaphylaxis (76.8%). 97.9% HCPs agreed that penicillin skin test was valuable to predict the allergic reaction. More than 80% of the respondents would take patients’ allergic history before drug administration, while 75.5% agreed that they recognize and manage drug allergy timely when it occurs. Conclusions: Drug allergy was often diagnosed and managed inadequately, regardless of practice location, employment status and speciality in eastern India. The HCPs demonstrated a low level of knowledge regarding DA. Advanced education is urgently needed for better understanding and filling the gaps that exist in the knowledge and clinical practice of DA.